BEYOND DIGITAL LITERACY: EVALUATION OF THE DIGITAL INTELLIGENCE OF STUDENTS AND HEALTHCARE WORKERS - Branco, Gilberto Vieira; Chagas, Deysianne Costa das; Lopes, Luciano Rodrigo; Pisa, Ivan Torres; Silva, Angélica Baptista (Revista Interfaces: Saúde, Humanas e Tecnologia, 2025)
The concept of Health Digital Intelligence (HDI), which encompasses digital literacy, refers to the set of competencies, knowledge, skills, attitudes, and values that enable individuals to effectively use digital information and communication technologies in their health-related activities. Recognizing the urgency and necessity of HDI, the Ministry of Health’s Digital Health Strategy 2020-2028, Brazil, underscores its importance. This article describes the development of a self-assessment test for HDI aimed at students and healthcare workers. This quantitative, cross-sectional, and descriptive study adopted the Common Framework for Digital Literacy, Skills, and Readiness, addressing digital competencies such as identity, use, safety, security, emotional intelligence, communication, literacy, and rights. The development stages included a literature review, test creation, expert evaluation, volunteer application, result analysis, discussion, and adjustments. In the first application, 292 participants responded to 44 statements, while in the second, 79 volunteers responded to 56 statements. An individual digital report was provided with a literacy score, highlighting profiles of digital citizenship, digital creativity, and digital competitiveness, as well as strengths and weaknesses in digital health literacy. Future studies should explore the application of the full HDI model and its relationship to the digital literacy maturity of students, healthcare professionals, patients, and citizens, aiming to significantly enhance the quality of healthcare delivery.